2021
DOI: 10.1038/s41541-021-00379-4
|View full text |Cite
|
Sign up to set email alerts
|

Deimmunization of flagellin for repeated administration as a vaccine adjuvant

Abstract: Flagellin, a protein-based Toll-like receptor agonist, is a versatile adjuvant applicable to wide spectrum of vaccines and immunotherapies. Given reiterated treatments of immunogenic biopharmaceuticals should lead to antibody responses precluding repeated administration, the development of flagellin not inducing specific antibodies would greatly expand the chances of clinical applications. Here we computationally identified immunogenic regions in Vibrio vulnificus flagellin B and deimmunized by simply removing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Studies have shown that the agellin is mainly composed of four domains: D0, D1, D2, and D3. The D0 and D1 domains located at the N/C ends of agellin are mainly composed of highly conserved α-helix and are the main area for exerting adjuvant functions; the D2 and D3 domains located in the HVR of agellin are highly variable, which mainly determines the antigenicity, and can reduce its antigenicity by deleting these domains (Liu, et al 2010;Khim, et al 2021). The results of structural prediction and analysis of FliC EcN are consistent with previous research.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the agellin is mainly composed of four domains: D0, D1, D2, and D3. The D0 and D1 domains located at the N/C ends of agellin are mainly composed of highly conserved α-helix and are the main area for exerting adjuvant functions; the D2 and D3 domains located in the HVR of agellin are highly variable, which mainly determines the antigenicity, and can reduce its antigenicity by deleting these domains (Liu, et al 2010;Khim, et al 2021). The results of structural prediction and analysis of FliC EcN are consistent with previous research.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of GPGPG linkers, these linkers can stimulate T-helper responses and the conformationally-dependent immunogenicity of helper and antibody epitopes 57 59 . In this study, to compensate for these vaccines' low immunogenicity, the D0/D1 domains of the flagellin protein from S. Typhimurium bacteria were utilized as an adjuvant to boost the effectiveness of immune system stimulation 60 . Also, The EAAAK linker was employed to connect the D0/D1 domains at the N-terminal region of the multi-epitope sequence .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ANGPTL3 is an attractive target for in vivo gene editing. Furthermore, anti‐dyslipidemia vaccine therapies targeting ANGPTL3 will be a hot research topic 183 . Of course, the long‐term safety and cost‐effectiveness of these agents remain to be demonstrated in ongoing and future clinical trials 137 …”
Section: Drug Development Of Targets Based On Gwas Wgs and Wes Discov...mentioning
confidence: 99%